Relationship between the armed arm`s motor response and muscle activation time during the lunge in fencers of varied ability - Balkó, Š.; Heidler, J.; Jelinek, M. (Journal of Human Sport & Exercise, 2018)
The present work studied potential differences in activation times of selected muscles associated with the motor responses of the armed arm and differences in selected muscle pairs activation during the fencing lunge. Twenty-eight fencers (epée fencers, aged 22.1 ± 5.4 years) grouped into elite and beginning skill levels, participated in this study. Surface electromyography was used to determine muscle activation time (time period measured from visual stimulus occurrence to the moment of muscle activation threshold detection). For motor response, we measured the time between visual stimulus occurrence and armed arm movement. A significant difference was found between elite and beginning fencers in the motor response of the armed arm. Detection of armed arm`s motor response was significantly later in beginners. Greater time disparities between arm`s motor response and muscle activation time of the m. rectus femoris on the front/lunge side was also found in beginners. Lastly, difference was detected between elite and beginning fencers regarding the muscle activation time of selected muscle pairs. Future studies and trainers can use these results to further explore key areas of motor control and biomechanics for improving of fencing performance.